A Mixed Methods Approach to Identify Cognitive Warning Signs for Suicide Attempts. Issue 4 (1st October 2016) - Adler, Abby; Bush, Ashley; Barg, Frances K.; Weissinger, Guy; Beck, Aaron T.; Brown, Gregory K.
Abstract : This study used a mixed methods approach to examine pathways to suicidal behavior by identifying cognitive warning signs that occurred within 1 day of a suicide attempt. Transcripts of cognitive therapy sessions from 35 patients who attempted suicide were analyzed using a modified grounded theory approach. Cognitive themes emerging from these transcripts included: state hopelessness, focus on escape, suicide as a solution, fixation on suicide, and aloneness. Differences in demographic and baseline diagnostic and symptom data were explored in relation to each cognitive theme. We propose a potential conceptual model of cognitive warning signs for suicide attempts that requires further testing.